THE INFLUENCE OF PRODUCT QUALITY, PRICE, AND E-WOM ON CUSTOMER LOYALTY AT NAMA BAIK CAFÉ SURABAYA - Azriel, Aubrey; Sutanto, J.E (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to determine the influence of product quality, price, and E-WOM on customer loyalty at Nama Baik Café Surabaya. Design/methodology/approach – The population used is all café visitors in Surabaya, the number of which is unknown. This research uses a non-probability sampling method and purposive sampling technique. The required criteria are consumers of Nama Baik Café in Surabaya who have made a minimum of 2 transactions, aged between 21 and 50 years old, and have an Instagram account. Online questionnaires distributed to 150 respondents and the data was processed using SPSS 20 program. Findings – The results of the research analysis is, it is found that all the variables studied influenced customer loyalty significantly, either partially or simultaneously.